Barrier function of the nasal mucosa in health and type‐2 biased airway diseases. Issue 3 (13th January 2016) - Zhang, N.; Van Crombruggen, K.; Gevaert, E.; Bachert, C.
Abstract: The mucosal lining of the upper airways represents the outer surface of the body to the ambient air and its contents and is prepared for it as the first line of defense. Apart from the well‐described physical barrier and the mucociliary clearance, a variety of systems, including the airway microbiome, antimicrobial proteins, damage‐associated molecular patterns, innate lymphoid cells, epithelial‐derived cytokines and chemokines, and finally the adaptive immune system, as well as eosinophils as newly appreciated defense cells form different levels of protection against and response to any possible intruder. Of interest especially for allergic airway disease, mucosal germs might not just elicit a classical Th1/Th17‐biased inflammatory response, but may directly induce a type‐2 mucosal inflammation. Innovative therapeutic interventions may be possible at different levels also; however, whether modulations of the innate or adaptive immune responses will finally be more successful, and how the correction of the adaptive immune response might impact on the innate side, will be determined in the near future.